IMPLEMENTASI ALGORITMA LEBAH DAN ALGORITMA SEMUT UNTUK MENENTUKAN RUTE TERPENDEK DALAM PROSES MONITORING WAJIB - Mohammad Wandy; Yuri Yudhaswana Joefrie; Rizka Ardiansyah; Dwi Shinta Angreni; Nouval Trezandy Lapatta (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The application of optimization algorithms to determine the shortest route is one effective approach to improving operational efficiency in various fields, including taxpayer monitoring. This study aims to implement two metaheuristic algorithms, namely the Ant Colony Optimization (ACO) algorithm and the Bee Algorithm, to identify the shortest routes for tax officers who are required to visit multiple taxpayer locations. In this study, both algorithms were tested using a dataset containing the locations of taxpayers that need to be monitored, with the objective of optimizing travel routes in order to reduce the total travel distance. The results show that both algorithms are capable of finding optimal or near-optimal solutions to the shortest path problem in the context of taxpayer monitoring. Although ACO is more effective in producing higher-quality solutions, the Bee Algorithm is faster in finding solutions, albeit with slightly less optimal results. This study also emphasizes the importance of algorithm parameter settings, such as the number of ants, the size of the bee colony, and the pheromone evaporation rate, which significantly affect solution quality and computation time.